Augmented Reality Book Development: Enhancing Fifth Grade Students' Understanding of Global Diversity - Bayu Satryo; Wuri Wuryandani (LPPM Undiksha, 2025)
Learning about global diversity at the elementary school level often remains abstract and lacks contextual relevance, causing students to experience difficulties in developing a deep understanding of cross-cultural concepts. This study aimed to develop an Augmented Reality (AR) Book incorporating cultural diversity content and to evaluate its effectiveness in enhancing global diversity awareness among fifth-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE development model. The developed product underwent validation by subject-matter and media experts, product trials, and effectiveness testing through pre-test and post-test designs involving experimental and control groups. The main findings indicate that the development of an augmented reality-based book significantly improved fifth-grade students’ understanding of global diversity concepts. The AR book successfully integrated narrative text, interactive illustrations, and three-dimensional objects accessible via mobile devices, thereby creating a more engaging and meaningful learning experience. It can be concluded that this medium is effective as an alternative interactive learning tool for enhancing students’ understanding and awareness of global diversity. The implications of this study suggest that the integration of augmented reality technology in elementary education holds considerable potential to transform how students comprehend global concepts and diversity values. The use of AR-based books not only enriches learning experiences but also supports the development of 21st-century competencies.